2008
DOI: 10.1007/s10522-008-9199-6
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin mediated lifespan extension in Caenorhabditis elegans is modulated by age-1, daf-2, sek-1 and unc-43

Abstract: The nematode Caenorhabditis elegans responds to flavonoid-rich diets with improved health and longevity. The precise mechanism(s) responsible for this remains to be identified, but is believed to be linked to the highly antioxidative properties of flavonoids. This study provides a dissection of lifespan modulation by the flavonoid quercetin. In detail, quercetin was shown not to act as a simple antimicrobial agent or exclusively via radical scavenging capacities. Likewise, lifespan extension had no effect on r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
133
3
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(157 citation statements)
references
References 70 publications
12
133
3
2
Order By: Relevance
“…This is not surprising considering that individual components in the OSR-1/UNC-43/SEK-1 pathway have been reported to differentially mediate the prolongevity effects of different phytochemicals. For instance, SEK-1, but neither OSR-1 nor UNC-43, is required for tannic acid-induced longevity (Saul et al 2010), while SEK-1 and UNC-43, but not OSR-1, are required for quercetin-induced longevity in C. elegans (Pietsch et al 2009). In addition, SEK-1 can regulate pathogen resistance independent of UNC-43 and OSR-1 (Kim et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is not surprising considering that individual components in the OSR-1/UNC-43/SEK-1 pathway have been reported to differentially mediate the prolongevity effects of different phytochemicals. For instance, SEK-1, but neither OSR-1 nor UNC-43, is required for tannic acid-induced longevity (Saul et al 2010), while SEK-1 and UNC-43, but not OSR-1, are required for quercetin-induced longevity in C. elegans (Pietsch et al 2009). In addition, SEK-1 can regulate pathogen resistance independent of UNC-43 and OSR-1 (Kim et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The heat shock assay was performed as described previously (Pietsch et al 2009;Strayer et al 2003) with some modifications. CBE-pretreated L4/young adult stage worms and controls were transferred to CBE supplemented (2 mg/mL) plates and regular NGM plates, respectively.…”
Section: Stress Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the nine studies on quercetin, seven reported quercetin as prolonging lifespan at concentrations ranging from approximately 70 to 200 µM (35)(36)(37)(38)(39)(40)(41) . One study supplementing quercetin at 166 µM could not detect lifespan extension (42) , another study applying quercetin at 50 and 250 µM reported no change and a decrease in lifespan, respectively (43) .…”
Section: Flavonoids and The Lifespan Of The Worm Caenorhabditis Elegansmentioning
confidence: 99%
“…However, in an age-1 mutant (phosphoinositide-3-kinase subunit p110 homologue) catechin increased lifespan, while quercetin did not. In turn, catechin failed to increase lifespan in an akt-2 (AKT homologue) mutant, while quercetin could K. Pallauf et al 158 prolong lifespan in these worms (30,37) . In contrast to quercetin and catechin, the life-expanding impact of icariside II, myricetin, cocoa powder and purple wheat extract was abolished by mutating daf-16, the worm FOXO homologue (45,46) .…”
Section: Studies In Mutantsmentioning
confidence: 99%